32. THE CHARACTERISTICS OF COMPREHENSIVE DEVELOPMENT OF CHILDREN UNDER 2 YEARS OF AGE HOSPITALISED AT CHILDREN'S HOSPITAL 1 (Vietnam Journal of Community Medicine, 2024)
Methods: Case series from November 2023 to September 2024 at Children's Hospital 1.Results: Among 201 patients of a pilot surveillance, male/female ratio=132 (65.7%)/69 (34.3%), median (interquartile range) age was 15.0 (11.0 – 21.5) month. The proportions of children with anemia, tooth decay, eye problems, and ear problems were 27.9%, 15.9%, 7.0%, and 1.5%, respectively. Appropriate diet, age-appropriate nutrition, and nutritional changes when suffering from disease accounted including 56.7%; 68.7%, and 47.8%; respectively. In term of the physical and nutritional development, the proportions of normal development, mild malnutrition, moderate malnutrition, severe malnutrition, risk of overweight, overweight, and obesity accounted for 67.2%, 17.4%, 5.5%, 2.5%, 4.0%, 2.0%, and 1.5%; respectively. Children 12 month old mainly had problems in cognition (understanding simple questions 83.9%; language (speaking at least 3 simple words 84.9%); and motor skills (knowing how to stand up when pulled by the hand or walk when someone leads the hand 87.0%). The 18-month-old children mainly had issue in language-communication with saying at least 20 single words and saying 4 consonants both constituted only 86.4%. Meanwhile, 24-month-old children have motor problems with walking 2 steps backward without assistance 83.3% and starting to try running 89.4%, 29.4% of direct caregivers do not show interest in the child, 37.3% of family members do not know how to make the child feel comfortable and show affection, and the rate of fathers who do not participate adequately in child care is 28.9%.Conclusion: The study emphasizes the importance of early intervention to improve the comprehensive development of children.